FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KESEPIAN PADA LANSIA - Eva Fitriana; Rina Puspita Sari; H.A.Y.G Wibisono (Nusantara Hasana Journal, 2021)
Loneliness is a feeling of being left out, being separated from others because they feel different from others, being excluded from the group, feeling unnoticed by the people around them, being isolated from the environment and as well. Purpose: to investigate to describe the factors associated with loneliness in the elderly. Methods: literature review with a prism model obtained from Google Scholar and Mendeley, published in 2015-2020. Result: in the literature review above, there are factors associated with loneliness in the elderly, namely: social interaction, stress, spirituality and family support. This is from several articles that there is a relationship between the level of loneliness and social interaction in the elderly, there is a relationship between stress and the level of loneliness in the elderly, there is a relationship between spirituality and the level of loneliness in the elderly.